2017
DOI: 10.1093/hmg/ddx065
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A2 links poor myofiber repair with inflammation and adipogenic replacement of the injured muscle

Abstract: Repair of skeletal muscle after sarcolemmal damage involves dysferlin and dysferlin-interacting proteins such as annexins. Mice and patient lacking dysferlin exhibit chronic muscle inflammation and adipogenic replacement of the myofibers. Here, we show that similar to dysferlin, lack of annexin A2 (AnxA2) also results in poor myofiber repair and progressive muscle weakening with age. By longitudinal analysis of AnxA2-deficient muscle we find that poor myofiber repair due to the lack of AnxA2 does not result in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 65 publications
5
56
0
Order By: Relevance
“…• Leakage of damage-associated molecules such as annexin A2 from dysferlin-deficient myofibers [211] through sarcolemma lesions [210], • Intrinsic pro-inflammatory signaling of dysferlin-deficient muscle fibers [118,212], •…”
Section: Inflammatory Processesmentioning
confidence: 99%
“…• Leakage of damage-associated molecules such as annexin A2 from dysferlin-deficient myofibers [211] through sarcolemma lesions [210], • Intrinsic pro-inflammatory signaling of dysferlin-deficient muscle fibers [118,212], •…”
Section: Inflammatory Processesmentioning
confidence: 99%
“…It is also worth noting that there were significant differences in the pre-TBI baseline levels in the grip and the Rotor Rod tests between WT and A2KO sham groups. The poorer performance of motor function in A2KO mice was speculated upon by a recent study, which reported that A2KO mice had a mild but progressive muscle weakness in locomotor activity [21]. Therefore, the decline of muscle strength or the worse locomotor activity of A2KO mice might also contribute to the worse sensorimotor function deficits after TBI.…”
Section: Discussionmentioning
confidence: 98%
“…The presence of dysferlin in vesicles or other membranous organelles seems to be important for such functions [5]. Annexin A2 is also critical for plasmalemma repair [4,49], and its ablation causes progressive muscle weakening [49]. Interplay between dysferlin, annexin A2, and actin remodeling has been observed during plasmalemmal repair.…”
Section: Discussionmentioning
confidence: 99%